Pregnancy in women with Hereditary Angioedema due to C1-inhibitor deficiency: Results from the ITACA cohort study on outcome of mothers and children with in utero exposure to plasma-derived C1-inhibitor - Triggianese, P.; Senter, R.; Petraroli, A.; Zoli, A.; Lo Pizzo, M.; Bignardi, D.; Di Agosta, E.; Agolini, S.; Arcoleo, F.; Rossi, O.; Modica, S.; Greco, E.; et al. (Frontiers in Medicine, 2022)
Background In women with Hereditary Angioedema (HAE) due to C1-inhibitor (C1INH) deficiency (C1INH-HAE), pregnancy counseling and treatment can be challenging. Despite the evidence of the immediate favorable outcome and safety of plasma-derived (pd)C1INH concentrate, there are no data regarding any difference among women who underwent or not pdC1INH during pregnancy or on children with in utero exposure to pdC1INH. The present interview study aimed at analyzing outcome of C1INH-HAE mothers and children according to pdC1INH-exposure during pregnancies. Methods C1INH-HAE women who experienced at least 1 pregnancy were included from seven centers of the Italian Network for Hereditary and Acquired Angioedema (ITACA). The interview study retrospectively analyzed pregnancies who underwent (group 1) or not (group 2) pdC1INH. The overall goals of the study included immediate and long-term outcomes, in terms of outcomes in the time interval between pregnancy and survey. Results A total of 168 pregnancies from 87 included women were analyzed. At term delivery (>37 gestation-week, GW) has been registered in 73.8% of cases, while spontaneous abortion (SA) occurred in 14.2% of cases with a mean GW 7 ± 2. The group 1 including pdC1INH-treated pregnancies comprised a third of the cohort (51/168, time interval 1.5 ± 10.4 yrs), while the group 2 represented 69.6% (117/168, time interval 32.8 ± 14 yrs). The same prevalence of SA occurred when comparing group 1 (11.7%) with group 2 (15.4%) with a similar GW at SA. The group 1 was older at the pregnancy time and younger at the interview than the group 2 (P < 0.01 for both); moreover, the group 1 showed a higher prevalence of cesarean delivery (P < 0.0001). The overall prevalence of obstetrical syndromes was similar between two groups: however, gestational diabetes was described only in pdC1INH-untreated pregnancies. In utero pdC1INH-exposed children (n = 45) did not show differences compared with unexposed ones (n = 99) in neonatal short-term outcomes. Conclusion Through appropriate management and counseling, most of C1INH-HAE women undergo successful pregnancy and delivery. For pregnant C1INH-HAE women being treated with pdC1INH, our findings are reassuring and might lead to an improvement of both the knowledge about treatments and the experience of HAE itself.